2020
DOI: 10.1007/s12649-020-01193-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Thermal and Mechanical Properties of Clay Reinforced with Typha australis: Influence of Length and Percentage of Fibers

Abstract: This study presents the elaboration and characterization of a composite material based on Typha australis and clay for the use of an innovative building material in construction. For this purpose, various percentages ranging from 0 to 55% with a pitch of 15 were used. The aim is to find a better compromise between the thermal and mechanical properties of this composite material. According to this, the influence of the length of the 1 cm and 3 cm fibers was studied. As Typha australis is very porous, the hydric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…As the density of the typha increases, the particles are more and more in contact releasing the air contained inside and between the particles which favors the increase of the thermal conductivity. The thermal conductivity value of typha obtained is similar to that obtained by Ba et al (2021) which is 0.061 W/(m K) for a density of 60 kg/m 3 . This difference can be explained by the nature of the typha, the conservation method, its water content, or the experimental conditions.…”
Section: Resultssupporting
confidence: 85%
“…As the density of the typha increases, the particles are more and more in contact releasing the air contained inside and between the particles which favors the increase of the thermal conductivity. The thermal conductivity value of typha obtained is similar to that obtained by Ba et al (2021) which is 0.061 W/(m K) for a density of 60 kg/m 3 . This difference can be explained by the nature of the typha, the conservation method, its water content, or the experimental conditions.…”
Section: Resultssupporting
confidence: 85%
“…. ) constituted an innovative and effective way of generating more pores in the fired bricks [18][19][20][21][22][23][24][25][26]. It was shown that a small quantity of additives (usually less than 10% by weight), which burns during the firing process, leads to an increase in the porosity of the brick and thus to a decrease in thermal conductivity.…”
Section: Structure and Texture Of Lignocellulosic Biomassmentioning
confidence: 99%
“…which is a plant that grows in abundance in the Senegal River valley [6]. This plant has good thermophysical properties, it has a thermal conductivity about 0.06 W/mk [7]. This article aims to show the impact of the length of plant fibers and their percentages on the thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%